Walker Empowering Women in Meridian - Parajuli, Raju (Tribhuvan Journal, 2023)
With the picture of personal struggle to overcome the patriarchal society, Alice Walker has concentrated on the empowerment of female values for the establishment and preservation of social and individual female identity in Meridian. Portrayed as a poor, uneducated, and a black girl, Meridian faces social and culturally harsh treatment and black males have behaved her as a toy resulting in double patriarchy. Her attachment with the Civil Rights Movement has brought a transformation and realization within her, which has ultimately enabled her to exist and revolt against male hegemony. Following the feminism as its theoretical tool, this research examines on how a neglected, uneducated poor black girl Meridian transfers herself into an independent woman having her own identity with representative character of an empowered woman. This article tries to examine how Walker has empowered females in the novel, Meridian.